Fungal Genetics Stock Center Catalogue of Strains, 10th Edition - Kevin McCluskey; Michael Plamann (Fungal Genetics Reports, 2004)
Catalogue of Strains, 10th edition, 2004, supplement to Fungal Genetics Newsletter No. 51. This catalogue contains lists of materials held by the Fungal Genetics Stock Center.